HUBUNGAN DISIPLIN KERJA DENGAN KINERJA PEGAWAI PADA DINAS PENDAPATAN DAN PENGELOLAAN KEUANGAN DAERAH (DPPKD) KOTA CILEGON - Novika, Putri Wahyu (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2017)
The purpose of this research is to know the working discipline at the Office of Revenue and Financial Management of Cilegon City, to determine the performance of employees and to know the relationship of work discipline with the performance of employees at the Office of Revenue and Financial Management of Cilegon City. The research method used is a type of survey in assosiative method, while the data type of this research is quantitative data with the sample of 53 people. Statistical analysis used is the correlation coefficient at significance level Î± = 5%. Result of research: The correlation coefficient r = 0.9310, meaning there is a very strong relationship between work discipline with employee performance and is positive. The relationship is shown in a simple linear regression equation Å¶ = 0.57 + 1.01X. it can be concluded there is a very strong relationship between work discipline with employee performance of 86.66% while the rest of 13.332% is determined by other factors.